Pengaruh Koordinasi, Etika Kerja, dan Kedisiplinan Terhadap Kinerja Pegawai di Bagian Produk Hukum dan Persidangan Sekretariat DPRD Provinsi DKI Jakarta - Yulianti, Yulianti; Komalawati, Euis (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research is based on this background. The performance of employees in the legal products and conference section of the DKI Jakarta Provincial DPRD Secretariat is a crucial factor in ensuring an effective legislative and supervisory process. However, challenges such as lack of coordination, low work ethics, and inconsistent discipline often hinder the achievement of optimal performance. This research aims to identify the extent to which coordination, work ethics and discipline influence employee performance in this environment. This research uses a quantitative approach with survey methods. Data was collected through a questionnaire distributed to employees in the legal products and welfare section of the DKI Jakarta Provincial DPRD Secretariat. Data analysis was carried out using descriptive and inferential statistical techniques, including multiple linear regression, to examine the relationship between the variables of coordination, work ethics and discipline on employee performance. The research results show that coordination, work ethics and discipline have a significant influence on employee performance by 78.1%. Employees who have good coordination are able to complete tasks more effectively and efficiently. Discipline has a strong influence on performance, maintaining consistency and limiting employee time in carrying out tasks. This research concludes that to improve employee performance, improvements are needed in terms of coordination, work ethics and employee discipline. Efforts are needed to improve coordination, work ethics and employee discipline. Recommendations that can be given based on the results of this research are the importance of implementing training programs and development that focuses on improving coordination, work ethics and employee discipline to achieve better performance.